DAMPAK PENGUNGKAPAN NON-FINANSIAL (DIGITAL TRANSPARANCY) TERHADAP EFEKTIVITAS AUDIT DAN PRAKTIK MANAJEMEN LABA PADA PERUSAHAAN TEKNOLOGI DI INDONESIA PERIODE 2022 – 2024 - Dhani Wirianto (Program Studi Bisnis Digital, Fakultas Ekonomi dan Bisnis, Universitas Riau Kepulauan, 2025)
This study aims to analyze the impact of non-financial disclosure (digital transparency) on audit effectiveness and earnings management practices in technology companies listed on the Indonesia Stock Exchange for the period 2022–2024. A quantitative approach was used in this study, collecting data through a survey of 100 respondents, consisting of auditors and financial managers from technology companies. The analysis technique used is linear regression to examine the relationship between digital disclosure and the two variables. The results show that although there is a relationship between digital disclosure and audit effectiveness as well as earnings management practices, this relationship is not statistically significant. This finding provides important contributions to the development of digital transparency and earnings management theories and offers practical insights for technology companies to improve audit quality and reduce earnings management practices through better disclosure policies. The study also highlights the need for other factors to enhance audit quality and earnings management in technology companies.